q-1/3=-2/3

Simple and best practice solution for q-1/3=-2/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for q-1/3=-2/3 equation:



q-1/3=-2/3
We move all terms to the left:
q-1/3-(-2/3)=0
We get rid of parentheses
q-1/3+2/3=0
We multiply all the terms by the denominator
q*3-1+2=0
We add all the numbers together, and all the variables
q*3+1=0
Wy multiply elements
3q+1=0
We move all terms containing q to the left, all other terms to the right
3q=-1
q=-1/3
q=-1/3

See similar equations:

| 8(4x─1)─12x=11(2x─6) | | 9x=2x-1 | | 54-2x=4x+36 | | (8x-16°)+(10x-32°)=180° | | t*8/3=336 | | 1/3(m-5)=3/4 | | 2x-5-4x+6=x | | 5/2x+2=0 | | 4.5x=2x-1 | | x*2/5=26 | | -3+x=-80 | | 2x-15=3x-20. | | (2/5)*x=26 | | 5v+8=-6+3v | | 9-x=-450 | | x^2+10x=-25. | | x^2=5x+36x2=5x+36 | | 14x-(3x-7)=95 | | m-8=18 | | 9n+5=5 | | 12g+8g=-12+11 | | 3(2x-3)-9=3x-27. | | 3x+20+2x=+x+40 | | 3x+20=+2x+x+40 | | (x+1)+5=3/2x+2 | | 3(2x+4)=18​ | | 4^(2x+7)=〖32〗^x | | 3x+20)=(2x+40 | | (3x–7)+55+(x+20)=180 | | -6(3+3x)=-4-4x | | 5(x-2)=5x= | | 20-5(p+1)+3=-(2p-15) |

Equations solver categories